2010
DOI: 10.1016/j.math.2010.06.007
|View full text |Cite
|
Sign up to set email alerts
|

A tissue velocity ultrasound imaging investigation of the dorsal neck muscles during resisted isometric extension

Abstract: Persons with neck pain exhibit altered patterns of muscle patterning, but limited investigations have been carried out on these alterations or muscle patterning in healthy volunteers. This study investigated the tissue motion of the dorsal neck muscles at the C4 segmental level in 15 healthy subjects during manually resisted head extension. Doppler-based tissue velocity ultrasound imaging (TVI) was used to detect regional tissue deformation, providing indirect evidence of inter-muscular movement patterning. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 33 publications
(56 reference statements)
0
8
0
Order By: Relevance
“…Ultrasound imaging enables non-invasive measurements of all five layers of the neck extensor muscles (Peolsson et al 2010;Rezasoltani et al 2013;Lee et al 2009). However, conventional ultrasound imaging (B-mode, M-mode and Doppler) reveal shape, thickness, deformation, strain and motion of muscles, not their stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…Ultrasound imaging enables non-invasive measurements of all five layers of the neck extensor muscles (Peolsson et al 2010;Rezasoltani et al 2013;Lee et al 2009). However, conventional ultrasound imaging (B-mode, M-mode and Doppler) reveal shape, thickness, deformation, strain and motion of muscles, not their stiffness.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20] Among these, ultrasound imaging is recognized as a reliable and valid method of muscle function evaluation in real time. 9,[21][22][23] In recent research studies, the interest in ultrasonography measurement of muscle dimensions has greatly increased. For instance, some studies reported dimensions of the CMM at rest or during an isometric head extension as an index for muscle activity using ultrasound.…”
mentioning
confidence: 99%
“…Ultrasound imaging could also be particularly useful to capture functional movements in real time 43 or verify the state and evolution of external muscle volume after a traumatic injury before the return of the player to the field. Since previous studies on the size of the muscles do not currently exist, the data presented in this paper can serve as a starting point for future research that may result in a consensus between the international federation and rugby leagues, once correlation to injury is established, by defining a minimum muscle size below which the player cannot get his "front row passport".…”
Section: Clinical Implicationmentioning
confidence: 99%